Supplementation with arginine in the diet of Nile tilapia reared in net cages - Fujimoto, Rodrigo Yudi; Santos, Rudã Fernandes Brandão; Pala, Gabriela; Gallani, Sílvia Umeda; Valladão, Gustavo Moraes Ramos; Morais, Gisele Cavalcante; Lee, James Tony; Sousa, Natalino Da Costa; Cunha, Fernanda Dos Santos; Maria, Alexandre Nizio; Carneiro, Paulo César Falanghe; Pilarski, Fabiana (Embrapa Secretaria de Pesquisa e DesenvolvimentoPesquisa Agropecuária Brasileira, 2019)
Abstract: The objective of this work was to evaluate the effect of dietary arginine concentrations on the health status of Nile tilapia (Oreochromis niloticus) cultivated in cages. The experiment was carried out in a completely randomized design with four treatments (2.3, 2.9, 3.5, and 4.1% arginine in dry matter) and three replicates, in 12 net cages of 8 m3, containing 4,000 sexually reverted tilapia (63±20 g, at 500 fish m-3). Fish productive performance and health were evaluated. Biochemical, hematological, and immunological parameters, as well as the morphological aspects of gills and liver, were evaluated. Arginine inclusion did not cause significant differences in fish growth performance. However, arginine supplementation at 3.5% concentration improved the biochemical parameters and leucocyte counts, consequently improving the immune system. The arginine concentration of 4.1% caused lipid degeneration, shown by the increase of alanine aminotransferase and the decrease of albumin, urea, lactate, and glucose. Arginine supplementation above 2.3% and below 3.5%, in the diets of tilapia reared in cages, improves fish immune system, without adverse morphological and physiological effects.

Resumo: O objetivo deste trabalho foi avaliar o efeito de concentrações de arginina dietética sobre a saúde da tilápia-do-nilo (Oreochromis niloticus), em tanques-rede. O experimento foi realizado em delineamento inteiramente casualizado, com quatro tratamentos (2,3, 2,9, 3,5 e 4,1% de arginina em relação à matéria seca na dieta) e três repetições, em 12 tanques-rede de 8 m3, com 4.000 tilápias revertidas sexualmente (63±20 g, 500 peixes m-3). Determinaram-se o desempenho produtivo e a saúde dos peixes. Avaliaram-se os parâmetros bioquímicos e hematoimunológicos e os aspectos morfológicos das brânquias e do fígado. A inclusão de arginina não proporcionou diferenças significativas no desempenho produtivo. Porém, a suplementação de arginina a 3,5% de concentração melhorou os parâmetros bioquímicos e de contagem de leucócitos, tendo consequentemente melhorado o sistema imunológico. A concentração de arginina a 4.1% causou degeneração lipídica, representada pelo aumento dos níveis da alanina aminotransferase e pela diminuição dos níveis de albumina, ureia, lactato e glicose. A suplementação com arginina acima de 2,3% e abaixo de 3,5%, nas dietas de tilápias criadas em tanques-rede, promove melhoras no sistema imunológico dos peixes, sem provocar efeitos morfológicos e fisiológicos deletérios.
Suplementação com arginina na dieta de tilápia-do-nilo produzida em tanques-rede
Keywords: Oreochromis niloticus; biochemistry; haematology; histology; nutritional requirement; Oreochomis niloticus; bioquímica; hematologia; histologia; exigência nutricional